2017
DOI: 10.1097/hjh.0000000000001445
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic versus isometric handgrip exercise in hypertension

Abstract: Isometric handgrip training, performed according to a typical protocol, did not reduce BP in hypertensive patients. Aerobic exercise, even as an uncontrolled and unsupervised exercise regimen, led to a significant reduction of ambulatory and office BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 29 publications
0
52
0
13
Order By: Relevance
“…Similarly, Stiller-Moldovan et al (2012) did not observe reduced ambulatory BP after 8 weeks of supervised isometric handgrip training in medicated hypertensive participants. Recently, Pagonas et al (2017) also did not observe reductions in ambulatory BP after supervised in hypertensive individuals. Previous studies have shown that ambulatory BP is a better marker of cardiovascular risk than office BPs (brachial or central BP) ( Huang et al, 2011 ).…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, Stiller-Moldovan et al (2012) did not observe reduced ambulatory BP after 8 weeks of supervised isometric handgrip training in medicated hypertensive participants. Recently, Pagonas et al (2017) also did not observe reductions in ambulatory BP after supervised in hypertensive individuals. Previous studies have shown that ambulatory BP is a better marker of cardiovascular risk than office BPs (brachial or central BP) ( Huang et al, 2011 ).…”
Section: Discussionmentioning
confidence: 93%
“…As published previously, the study size was calculated by the expected effect of exercise on BP (reduction of about 7 mmHg of the systolic BP) resulting in the recruitment of 75 patients. 11 This sample size ( n = 75) exceeded the necessary sample size ( n = 45) to detect the expected effect on HDLox based on a standard deviation of 10%. Data were analyzed for normal distribution by the Kolmogorov–Smirnov test.…”
Section: Methodsmentioning
confidence: 94%
“…Skeletal muscle is the largest insulin-sensitive tissue in the body and is the major site for insulin-stimulated glucose utilization (Stump et al, 2006); thus, loss of muscle mass and muscle quality may play a critical role in the development of CMD (Atlantis et al, 2009;Butcher et al, 2018;Kim and Park, 2018;Li et al, 2018). Although the association between HGS and CMD was found in several studies (Kelley and Kelley, 2010;Peterson et al, 2016Peterson et al, , 2017Karvonen-Gutierrez et al, 2018;Li et al, 2018;Zhang et al, 2018), most studies are cross-sectional design (Dong et al, 2016;Peterson et al, 2016Peterson et al, , 2017Ji et al, 2018;Li et al, 2018;Zhang et al, 2018;Wu et al, 2019) and controversial results exist (Dong et al, 2016;Pagonas et al, 2017;Giglio et al, 2018;Ji et al, 2018). For example, Peterson et al (2017) analyzed the data from the U.S. National Health and Nutrition Examination Survey 2011-2012 and 2013-2014 combined surveys, and the 2011 wave of the China Health and Retirement Longitudinal Study, and found that normalized HGS was robustly associated with both CMD and physical disabilities in the United States and Chinese aging adults.…”
Section: Introductionmentioning
confidence: 99%